2019
DOI: 10.1097/md.0000000000017683
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes toward end-of-life care among community health care providers and its influencing factors in China

Abstract: A majority of nurses struggled with a negative emotion of anger, doubt, fear, or anxious, uncomfortable in the face of death and dying. However, little was known about community health care providers’ in China. Therefore, we conducted a study to investigate their knowledge and attitudes toward end-of-life care and analyze its influencing factors. To provide reference for developing effective strategies to promote end-of-life care in China.A total of 132 community health care providers of 10 community health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
(32 reference statements)
5
41
0
Order By: Relevance
“…Medical staff from level 3 hospitals may have more access to continuous hospice education and may have better knowledge of and attitudes towards hospice care than those from lower level hospitals; this might be beneficial for their hospice care self-efficacy [ 48 , 49 ]. However, studies showed Chinese health care providers in general lacked systematic and professional knowledge and skills for caring for terminal patients [ 50 – 52 ]. A survey investigated 141 trainees in the 2016 National Hospice and Palliative Medicine Training Program and found that only 21.3% had attended any hospice and palliative care course prior [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical staff from level 3 hospitals may have more access to continuous hospice education and may have better knowledge of and attitudes towards hospice care than those from lower level hospitals; this might be beneficial for their hospice care self-efficacy [ 48 , 49 ]. However, studies showed Chinese health care providers in general lacked systematic and professional knowledge and skills for caring for terminal patients [ 50 – 52 ]. A survey investigated 141 trainees in the 2016 National Hospice and Palliative Medicine Training Program and found that only 21.3% had attended any hospice and palliative care course prior [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high knowledge score of the principles of a good death among the study participants is likely to be an overestimate due to a positive marking bias as reflected by over 50% marking the two incorrect responses as correct. As expected, doctors who had been caregivers for a relative with a terminal illness were better informed of the concept of a 'good death' [23]. In Sri Lanka, physician aid-in-dying is illegal.…”
Section: Discussionmentioning
confidence: 63%
“…Our survey found that tertiary level hospitals accounted for 75% of the institutions providing hospice care services in the region in 2019. The development of hospice care in China was unbalanced with small coverage [15]. Additionally, the development of hospice care services had some problems, such as single form of service, lack of standard service content and unclear operation mode.…”
Section: Weaknessesmentioning
confidence: 99%
“…Third, hospice care was a special medical service, requiring high knowledge and skills of staff. However, currently, most practitioners in medical institutions in this region have not received formal professional education and training in hospice care services, and the professional knowledge and skills related to hospice care were insufficient [15][16][17]. None of the 182 hospice care practitioners surveyed had received any professional qualification training or assessment.…”
Section: Weaknessesmentioning
confidence: 99%